Economic Business Development for the People Through Optimizing the Role of Islamic Boarding Schools in a Pandemic Period - Murtiadi Awaluddin; Ilham Gani; Sri Prilmayanti Awaluddin (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2023)
The purpose of this study was to determine the model of developing the people's economic business through optimizing the role of pesantren during the pandemic and to design the role of pesantren in supporting village economic resilience. This type of research is a field research. The research location is located in Darud Da'wah Wal-Irsyad Islamic Boarding School (Ponpes) Mangkoso, Barru Regency. The approach in this research is a phenomenological approach and a participation action research approach. The analysis technique in this study uses Huberman and Miles qualitative analysis data. The conclusions of this study are (1) the economic business development model of the people through optimizing the role of Islamic boarding schools during the pandemic at the DDI Mangkoso Islamic Boarding School has been running well; (2) the role of pesantren in supporting village economic resilience is very potential.